Proposed Outer Continental Shelf oil and gas lease sale 46, Western Gulf of Alaska--Kodiak : draft environmental impact statement - United States. Bureau of Land Management. ([Anchorage, Alaska] : The Bureau, 1979)
Accompanying portfolio of 15 maps under title: West Gulf of Alaska (Kodiak #46). "1980"--Cover. Cover title: Western Gulf of Alaska--Kodiak. Bibliography: p. 1-17 (3rd group) Mode of access: Internet.